Experience of Psychosocial Formulation within a Biopsychosocial Model of Care for First- Episode Psychosis - Victoria Anne Cairns, Dr (International Journal of Psychosocial Rehabilitation, 2015)
Objectives: A biopsychosocial model of care (integrating biological and psychosocial supoprt) is often applied within Early Intervention for Psychosis services. The current study aims to explore the experience of people engaging with a process of psychosocial formulation whilst also being supported by clinicians representing a biological understanding of psychosis. Design: A qualitative design is used, with data collected through semi-structured interviews. Methods: 9 individuals from Early Intervention services were interviewed regarding their experience of engaging in psychosocial formulation whilst concurrently receiving ongoing support from a medical perspective. Results: 3 common themes were identified across the experience of the participants. These were (i) a joined-up ‘package’ of support (ii) formulation makes a distinctive contribution to the ‘package’ (iii) shaping the experience. Conclusions: The biopsychosocial model of care for first episode psychosis was experienced by participants as offering a sense of a coherent support ‘package’. This was multi-faceted, of which psychosocial formulation was identified as making a distinctive contribution. Participants also exerted agency upon their experience of the biopsychosocial model of care and were able to shape their support in a way that was most personally meaningful. Suggestion of the existence of a continuum of experience of psychosocial formulation within this context is discussed, in addition to implications for clinical practice regarding the need to enhance the malleable nature of the biopsychosocial model.